The Weight of Words: Italian Translation, Adaptation, and Effective Words in Marina Carr’s By the Bog of Cats… - Cutrale, Carlotta (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
Abstract Being able to translate emotions is at the very least a titanic task. It is almost impossible to translate the emotional drive that an actor conveys to his audience based on the words of a script. The aim of this study is to probe the unknown realm of emotions from one translation of the same text to another. In other words, this research will try to understand how it is possible to convey the same emotions as those conveyed by an actor on stage in a mere page of paper in a book. In order to try to find a solution to this dilemma, the text examined will be the work of Marina Carr, a famous Irish playwright, called By the Bog of Cats… (1998), a tragedy largely inspired on Euripides' Medea (431 BC) and plunged into the socio-cultural context of the Irish Midlands with the linguistic peculiarity of the so-called Midlands accent that Carr uses in its phonemic fashion. Therefore, in order to try to transfer from Irish-English to Italian the emotional weight and assortment that such a tragedy boasts, first of all a translation of the play into Italian will be carried out, in order to understand how words in their simplicity are rendered and interpreted by the translator always relating them to the potential interpretation of actors and actresses. Secondly, the adaptation of the Italian translation into the genre of a novel will take place in order to establish what emotional and metaphorical weight those words have, by removing the intervention of the actors from the translating and emotional equation and thus making the words on paper the interpreters of the drama on the page. Finally, the two translations will be compared in terms of syntax, semantics, metrics and rhetoric, analysing the different facets of the emotional perception of words and their inevitable linguistic choice.
Keywords: Literary Translation